42. The role of emphysema on radiation-induced lung toxicity and the feasibility of a "functional treatment plan". (December 2018) - Maddalo, M.; Moschini, I.; Benecchi, G.; Calabri, E.; Rossi, R.; Losardo, P.; Bergamini, M.L.; Dell'Anna, C.; Ceccon, G.; Grondelli, C.; Nurmahomed, S.; Gianni, S.; et al.
Abstract : Purpose: Although the relationship between pulmonary emphysema (PE) and pneumonitis after radiotherapy has been investigated in recent years, it remain controversial[1, 2] . The aim of this study was to retrospectively examine the role of PE on radiation-induced lung toxicity (RILT). The feasibility of a "functional treatment plan (FTP)", designed to spare the functional volumes of the lungs (FLV), was also investigated. Methods: 34 patients with NSCLC who underwent radiotherapy has been selected for this study. An expert radiologist analysed the first CT after-treatment and subdivided patients in two categories: RILT-1, 13 patients with no/low RILT; RILT-2, 21 patients with high RILT. Thresholds were applied on planning CT (before-treatment) to define PE (below −900  U) and FLV (between −899 and −500 HU). Through the Mann-Whitney test, RILT-1 and RILT-2 were compared in terms of PE volumes and of dosimetric parameters V5Gy and V20Gy of both total (DPTL) and functional lungs (DPFL). For patients who had considerable PE volumes, FTPs were developed based on VMAT technique. To selectively spare the FLV, arc sectors that involved parts of FLV were avoided and high-weight constraints for FLV were applied in the VMAT Optimizer. Results: PE volume was significantly higher in RILT-1 than in RILT-2 (p < 0.05). RILT-1 was characterised by significantly lower DPTL than RILT-2 and the difference become stronger when considering DPFL. The 66.7% of FTPs were not feasible because PE was irregularly distributed over the whole lungs volume. Regarding the remaining 33.3% of the FTPs, FLV Dmean averagely decreased by 0.67 Gy (0.25 < ΔDmean < 1.52 Gy). Conclusions: This study suggested that patients with emphysema were less subject to RILT. In addition, RILT was better associated with FLV exposure than total lung exposure. Therefore, a FTP would be desirable, but it's limited to a small number of cases depending on PE amount and distribution.